An integrated optimization model for the location of hydrogen refueling stations. (18th October 2018) - Li, Yushan; Cui, Fengming; Li, Lefei
Abstract: The widespread use of hydrogen fuel cell vehicles (HFCVs), as the cleanest fuel cell vehicle by far, aims to offer a promising solution in relieving the energy crisis and protecting the environment. To promote the widespread use of HFCVs, we should build a sufficient number of stations for HFCVs to foster refueling convenience. However, the high cost of refueling stations and the uncertainty of hydrogen fuel demand form a "Chicken and Egg" vicious cycle, which hinders the diffusion of HFCVs in the market. Aiming to explore a mutual interaction between hydrogen fuel cell vehicle (HFCV) sales and the number of refueling stations, this study proposes an integrated optimization model comprising the generalized Bass diffusion model (GBDM) and flow capturing location model (FCLM). The integrated optimization model is solved by using the capacitated FCLM algorithm and the designed solution process, and the results highlight that the long term location plan for a hydrogen refueling station network can meet the continuously increasing fuel demand while improving the utilization of refueling stations in practice. Such plan will contribute to promoting the diffusion of HFCVs in the market and protecting investors' interests, namely, by maximizing social benefits and economic value while realizing a win-win situation in the long term. The results also can provide managers with quantitative support for the construction of hydrogen refueling stations and the promotion of the HFCV market. Highlights: Develop a generalized Bass diffusion model for Chinese HFCVs. Develop an integrated optimization model for hydrogen refueling station following the diffusion rules of vehicle market. Make a long-term location plan for the hydrogen refueling station. Explore a positive interaction between hydrogen fuel cell vehicle (HFCV) sales and the number of refueling stations. The integrated optimization model demonstrates the general paradigm to break "Chicken and Egg" vicious cycle.